Soccer footedness and between-limbs muscle strength: Systematic review and meta-analysis - DeLang, M. D.; Rouissi, M.; Bragazzi, N. L.; Chamari, K.; Salamh, P. A. (International Journal of Sports Physiology and Performance, 2019)
Purpose: Limb dominance and consequent between-limbs muscle strength in soccer players should be explored to determine a standard musculoskeletal profile to maintain and establish during screening protocols and postinjury rehabilitation. The primary aim of this review was to identify dominant- vs non-dominant-lower-extremity muscle-strength characteristics of healthy soccer players, with secondary aims to consider available between-limbs outcome measures and directions for future research. Methods: Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines were followed. Five electronic databases were used for study identification with guidance from a medical librarian. Inclusion criteria consisted of studies employing a cross-sectional design assessing soccer players of all ages, genders, and levels of play that identified limb dominance and associated lower-extremity muscle strength as a main purpose of the experiment. Results: The literature search identified 3471 articles. After screening titles, abstracts, and full texts, 17 articles were included in the review. Peak torques and hamstring-to-quadriceps ratios via isokinetic dynamometry were commonly used, and subsequent meta-analyses were conducted to yield remarkable between-limbs symmetry. Additional results of individual studies also demonstrate symmetry, except 1 article of velocity-dependent measures that reported greater strength in the dominant limb. Conclusions: In soccer, between-limbs muscle strength measured by maximal isokinetic dynamometry demonstrates symmetry across ages, genders, and levels of play. Future testing using alternative measures that more specifically replicate the movement demands of soccer players may further classify between-limbs characteristics.